Opening of the central Atlantic Ocean: Implications for geometric rifting and asymmetric initial seafloor spreading after continental breakup. Issue 6 (26th June 2017) - Biari, Y.; Klingelhoefer, F.; Sahabi, M.; Funck, T.; Benabdellouahed, M.; Schnabel, M.; Reichert, C.; Gutscher, M.‐A.; Bronner, A.; Austin, J. A.
Abstract: Study of the deep structure of conjugate passive continental margins combined with detailed plate kinematic reconstructions can provide constraints on the mechanisms of rifting and formation of initial oceanic crust. In this study the central Atlantic conjugate margins are compared based on compilation of wide‐angle seismic profiles from NW Africa Nova Scotian and U.S. passive margins. The patterns of volcanism, crustal thickness, geometry, and seismic velocities in the transition zone suggest symmetric rifting followed by asymmetric oceanic crustal accretion. Conjugate profiles in the southern central Atlantic image differences in the continental crustal thickness. While profiles on the eastern U.S. margin are characterized by thick layers of magmatic underplating, no such underplate was imaged along the African continental margin. In the north, two wide‐angle seismic profiles acquired in exactly conjugate positions show that the crustal geometry of the unthinned continental crust and the necking zone are nearly symmetric. A region including seismic velocities too high to be explained by either continental or oceanic crust is imaged along the Canadian side, corresponding on the African side to an oceanic crust with slightly elevated velocities. These might result from asymmetric spreading creating seafloor by faulting the existing lithosphere on the Canadian side and the emplacement of magmatic oceanic crust including pockets of serpentinite on the Moroccan margin. After isochron M25, a large‐scale plate reorganization might then have led to an increase in spreading velocity and the production of thin magmatic crust on both sides. Key Points: Asymmetric spreading creating amagmatic crust on the Canadian side and magmatic oceanic crust on the Moroccan margin Oceanic crust in the Moroccan margin might have been modified and thickened by the presence of the Canary hot spot Thick layers of volcanic underplate and seaward dipping reflector sequences are imaged only along the U.S. continental margin